Toxoplasma gondii seroprevalence in the Iranian blood donors: A systematic review and meta-analysis - Foroutan, Masoud; Majidiani, Hamidreza; Hassanipour, Soheil; Badri, Milad (Heliyon, 2024)
The present systematic review and meta-analysis was done to assess the rate of Toxoplasma gondii (T. gondii) exposure among Iranian healthy blood donors. We searched four English (PubMed, Scopus, Web of Science, and Science Direct) and two Persian databases (Magiran and SID) as well as Google Scholar as a specialized article search engine using specific keywords for relevant papers from the inception up to November 30, 2023. In total, 19 studies enrolling 8226 apparently healthy blood donors were examined regarding T. gondii-specific IgG and/or IgM antibodies, among which 2666 [32.9% (95% CI: 25.3%–41.6%)], 168 [1.4% (95% CI: 0.9%–2.1%)], and 83 [1.7% (95% CI: 1.3%–2.1%)] subjects were seropositive regarding IgG, IgM, and both IgG/IgM antibodies, respectively. Five risk factors were significantly associated with T. gondii seroprevalence, including gender (OR = 1.98; 95% CI: 1.52–2.58; P < 0.001), contact with cat (OR = 2.41; 95% CI: 1.70–3.41; P < 0.001), contact with soil (OR = 2.83; 95% CI: 1.07–7.45; P = 0.035), consuming raw/undercooked meat (OR = 1.95; 95% CI: 1.03–3.70; P = 0.039), and raw/unwashed vegetables (OR = 1.70; 95% CI: 1.25–2.31; P = 0.001). A moderate rate of T. gondii exposure was found in the Iranian blood donors, with the association of several risk factors, including gender, contact with cat, contact with soil, consumption of unwashed vegetables and/or undercooked meat. Still, more studies are recommended regarding T. gondii exposure among blood donors in Iran.